Can Hong Kong price-manage its cross-harbor-tunnel congestion?. (December 2015) - Woo, C.K.; Cheng, Y.S.; Li, R.; Shiu, A.; Ho, S.T.; Horowitz, I.
Highlights: We estimate Generalized Leontief demand systems of Hong Kong's cross-harbor tunnel usage. We conclude that the traffic of the cross-harbor tunnels can be price-managed. The methodology can be used to analyze traffic demand in other toll roads, bridges and tunnels. Abstract: Hong Kong drivers face daily congestion, especially at the Cross Harbor Tunnel (CHT) whose tolls are substantially lower than those of the drivers' other two tunnel options: the Eastern Harbor Crossing (EHC) and the Western Harbor Crossing (WHC). In 2013, the Hong Kong Special Administrative Region (HKSAR) Government issued a consultation paper, seeking public comments on three toll-change proposals that would raise the CHT's tolls and lower the EHC's tolls. The WHC's tolls would remain unchanged due to its congested connecting roads. Using monthly crossing data available from the HKSAR's Transport Department for 2000–2012, this paper uses a Generalized Leontief demand system to document that the usage patterns of the three tunnels is price-responsive. Hence, we conclude that the proposed toll changes are likely to be effective in transportation demand management, by shifting a portion of the CHT's usage to the EHC and WHC, thereby relieving the CHT's congestion.